Opłata skarbowa w systemie prawa PRL na przykładzie ustawy z dnia 13 grudnia 1957 roku o opłacie skarbowej - Antonów, Dobrosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article is devoted to the Stamp Duty Act of 13 December 1957. It was the first piece of legislation regulating stamp duty in the Polish People’s Republic. It followed the premises of the Polish People’s Republic’s tax policy. Some of its regulations were incorporated into subsequent stamp duty acts from that period and have even survived the post-1989 transformations. In the article the author discusses the various elements of the Act and evaluates them from the point of view of the premises of tax policy of asocialist state and from the point of view of the essence of the duty as apublic levy.
Keywords: cło; opłata skarbowa; prawo Polskiej Rzeczypospolitej Ludowej; opłata; danina publiczna